2023
DOI: 10.1101/2023.03.29.534731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering novel TCF4-driven mechanisms underlying a common triplet repeat expansion-mediated disease

Abstract: The predominant cause of Fuchs endothelial corneal dystrophy (FECD) is a CTG repeat expansion (termed CTG18.1) situated within an intron of the transcription factor encoding gene,TCF4. Here we use a primary FECD case-derived corneal endothelial cell (CEC) system to enhance our understanding of multiple pathogenic processes underlying CTG18.1-mediated FECD. We define differential gene expression and alternative splice events using long- and short-read RNA-seq datasets generated from 15 biologically independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(190 reference statements)
1
1
0
Order By: Relevance
“…A strong correlation between CTG18.1 expansion length in peripheral blood leukocytes and molecular hallmarks of pathology in the corneal endothelium, including the presence of nuclear CUG-specific RNA foci and isoform-specific patterns of TCF4 downregulation, is well documented (Zarouchlioti et al 2018;Hu et al 2018;Powers et al 2022;Bhattacharyya et al 2024). Our study has shown that the mean repeat length in mono-allelic expanded CEC lines is 4.4 to 17.0-fold longer than in leukocyte gDNA samples.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A strong correlation between CTG18.1 expansion length in peripheral blood leukocytes and molecular hallmarks of pathology in the corneal endothelium, including the presence of nuclear CUG-specific RNA foci and isoform-specific patterns of TCF4 downregulation, is well documented (Zarouchlioti et al 2018;Hu et al 2018;Powers et al 2022;Bhattacharyya et al 2024). Our study has shown that the mean repeat length in mono-allelic expanded CEC lines is 4.4 to 17.0-fold longer than in leukocyte gDNA samples.…”
Section: Discussionsupporting
confidence: 73%
“…To overcome this limitation and acquire enough cells for the OGM protocol (approximately 1 million cells per sample), we used primary CEC cultures generated from endothelial keratoplasty specimens removed following planned corneal surgery to analyse CEC-specific gDNA. We have previously demonstrated that these primary CEC cultures robustly maintain the biomarkers of CTG18.1-mediated disease and generate a pure corneal endothelial cell model that enables the investigation of FECD in a disease-relevant cell context (Zarouchlioti et al 2018;Bhattacharyya et al 2024). We acquired paired biosamples (corneal endothelial specimens and peripheral blood leukocytes) from 9 FECD patients to directly compare instability levels between the affected and unaffected cell types.…”
Section: Ctg181 Displays Tissue-specific Somatic Instabilitymentioning
confidence: 99%